2013
DOI: 10.1007/s11011-013-9414-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant treatment strategies for hyperphenylalaninemia

Abstract: Hyperphenylalaninemia (HPA) leads to increased oxidative stress in patients with phenylketonuria (PKU) and in animal models of PKU. Early diagnosis and immediate adherence to a phenylalanine-restricted diet prevents HPA and, consequently, severe brain damage. However, treated adolescent and adult PKU patients have difficulties complying with the diet, leading to an oscillation of phenylalanine levels and associated oxidative stress. The brain is especially susceptible to reactive species, and oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 94 publications
1
9
0
Order By: Relevance
“…Physical exercise has been shown to improve brain function by preventing oxidative stress in PKU . Several antioxidant supplementations have been evaluated and may be a complement or an alternative to a restrictive diet for adolescent and adult PKU patients with poor compliance (Mazzola et al 2013). In this way, supplementation with L-carnitine and selenium seems to prevent oxidative stress observed in hyperphenylalaninemia .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Physical exercise has been shown to improve brain function by preventing oxidative stress in PKU . Several antioxidant supplementations have been evaluated and may be a complement or an alternative to a restrictive diet for adolescent and adult PKU patients with poor compliance (Mazzola et al 2013). In this way, supplementation with L-carnitine and selenium seems to prevent oxidative stress observed in hyperphenylalaninemia .…”
Section: Discussionmentioning
confidence: 99%
“…Phenylketonuria (PKU, OMIM #26160) is an autosomal recessive disease caused by the deficiency of phenylalanine hydroxylase activity leading to an accumulation of phenylalanine (Phe) and its metabolites in blood and tissues of affected patients (Krause et al 1985;Mazzola et al 2013). Neonatal newborn mass-screening of this disorder allows early diagnosis and consequently a better and earlier dietary management leading to a normal development of PKU children (Groselj et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies demonstrated that T‐AOC was decreased in PKU (Sitta et al, 2009). GSH was reported to be decreased in erythrocytes, hippocampus and cerebral cortex by the administration of Phe in vitro to the hippocampus and cerebral cortex of rat brains (Mazzola et al, 2013; Fernandes et al, 2010). In the current study, it was worth to note that decreased T‐AOC and GSH in PKU patients seemed to correlate negatively with Phe level.…”
Section: Discussionmentioning
confidence: 99%